Mechanisms of acute adductor longus injuries in male football players: a systematic visual video analysis - Serner, A.; Mosler, A. B.; Tol, Johannes L.; Bahr, R.; Weir, A. (British Journal of Sports Medicine, 2019)
Background: Change of direction and kicking have been described as the main actions resulting in adductor longus injury. Video descriptions of inciting events are lacking. Objective: Perform a standardised visual video analysis of a series of acute adductor longus injuries in football. Study design: Cross-sectional. Methods: Video footage was reviewed by players, and assessed independently by five sports medicine professionals. Inciting events were described and categorised using standardised scoring, including playing situation, player/opponent behaviour, movement and body positions. Results: Videos of acute adductor longus injuries in 17 professional male football players were analysed. Most injuries occurred in non-contact situations (71%), following a quick reaction to a change in play (53%). Injury actions were: change of direction (35%), kicking (29%), reaching (24%) and jumping (12%). Change of direction and reaching injuries were categorised as closed chain movements (59%), characterised by hip extension and abduction with external rotation. Kicking and jumping injuries were categorised as open chain (41%), characterised by a change from hip extension to hip flexion, and hip abduction to adduction, with external rotation. Conclusion: Acute adductor longus injuries in football occur in a variety of situations. Player actions can be categorised into closed (change of direction and reaching) and open (kicking and jumping) chain movements involving triplanar hip motion. A rapid muscle activation during a rapid muscle lengthening appears to be the fundamental injury mechanism for acute adductor longus injuries. Abstract from author